Evaluasi Usabilitas Prototipe Sistem Bank Sampah Bangkitku : Pendekatan Gabungan Maze Testing dan SEQ - Sopia Ranty; Muhammad Roqib; Reni Aryani; Zainil Abidin; Noneng Marthiawati (Pusat Riset dan Inovasi Nasional, 2025)
Before an information system is implemented, usability evaluation is essential to ensure that the system is easy to learn, efficient to use, and aligned with user needs. This principle was applied to the prototype of the Bank Sampah Bangkitku Information System, a web-based platform developed to support waste bank operations in Jambi City. This study aimed to evaluate the usability level of the prototype by involving five administrators and five customers. Testing was conducted using Maze to assess learnability, efficiency, and error aspects, while the Single Ease Question (SEQ) questionnaire was employed to measure user satisfaction. The results showed a Maze Usability Score (MAUS) of 98 for administrators and 97 for customers, both falling into the “excellent” category. Most SEQ scores ranged between 6–7, indicating that users considered the system easy to use, efficient, and satisfactory. The evaluation also highlighted design strengths, including intuitive navigation, clear function labeling, and effective visual cues. With high usability scores, the prototype is proven feasible for real-world implementation as a digital solution to enhance waste bank management effectiveness and promote sustainable community participation.